The Effect of Net Income, Current Ratio, and Debt to Asset Ratio to Stock Price of Consumer Goods Industry Sector Listed in the Indonesia Stock Exchange (IDX) - Bella Febrina; Cindy; Wirda Lilia (Institute of Computer Science (IOCS), 2021)
The purpose of this research is to test and analyze the effect of net income, current ratio, and debt to asset ratio on the stock price of the consumer goods industry sector listed in the Indonesia Stock Exchange (IDX). This research uses a quantitative approach method. As the population, this research uses the consumer goods industry sector companies listed in the Indonesia Stock Exchange (IDX) in the period of 2015-2018. The method used in selecting the sample is purposive sampling which results in 17 companies selected as the sample of this research. This research works on secondary data taken from the Indonesia Stock Exchange website. The data of this research is then analyzed by using multiple linear regression analysis. The coefficient of determination is 43,5% which means that variation in stock price can be explained by the variation of net income, current ratio, and debt to asset ratio as far as 43,5%. The result shows that simultaneously, net income, current ratio, and debt to asset ratio have a significant effect on the stock price. Partially, net income has a positive and significant effect on stock price while the current ratio and debt to asset ratio have an insignificant effect on the stock price.